Etanercept Suppresses Arteritis in a Murine Model of Kawasaki Disease: A Comparative Study Involving Different Biological Agents - Ohashi, Ryuji (Hindawi Publishing Corporation, 2013)
Coronary arteritis, a complication of Kawasaki disease (KD), can be refractory to immunoglobulin (IVIG) treatment. To determine the most effective alternative therapy, we compared the efficacy of different agents in a mouse model of KD. Vasculitis was induced by injection of Candida albicans water-soluble fractions (CAWS) into a DBA/2 mouse, followed by administration of IVIG, etanercept, methylprednisolone (MP), and cyclosporine-A (CsA). At 2 and 4 weeks, the mice were sacrificed, and plasma cytokines and chemokines were measured. CAWS injection induced active inflammation in the aortic root and coronary arteries. At 2 weeks, the vasculitis was reduced only by etanercept, and this effect persisted for the subsequent 2 weeks. At 4 weeks, IVIG and CsA also attenuated the inflammation, but the effect of etanercept was more significant. MP exerted no apparent effect at 2 or 4 weeks. The suppressive effect exerted by etanercept on cytokines, such as interleukin- (IL-)6, IL-12, IL-13, and tumor necrosis factor-α (TNF-α), was more evident than that of others. The extent of arteritis correlated with the plasma TNF-α levels, suggesting a pivotal role of TNF-α in KD. In conclusion, etanercept was most effective in suppressing CAWS-induced vasculitis and can be a new therapeutic intervention for KD.